Investigation of a super-lift luo-converter used in solar panel system - Liu, Shuo. (2011)
With the increasing energy shortage and environmental pollution, the studies and applications of solar power have attracted growing interest among researchers in the relevant field. Although solar power has many advantages such as cleanness, renewability and environmental-friendliness, it is still inevitably affected by the changeable sunlight and weather condition. As a result, the output of a solar panel tends to be unstable. Furthermore, if the voltage variation is too large, it will have bad effect on loads or power grid. Super-Lift Luo-Converter has very high voltage transfer gain as well as many other advantages such as high efficiency, simple structure and low cost. A double closed-loop control has the ability to make the output voltage closely track a reference value. Therefore, in this project, a solar panel power system is designed using the Super-Lift Luo-Converter with a closed-loop control to obtain the desired output voltage. To make sure that the designed system met the design requirements, the open-loop and closed-loop simulations were carried out by using PSIM. The simulation results showed that the final output voltage was stable, which meant the designed solar panel system could effectively increase the stability of the output voltage. This project not only attempts to reflect the current development trend of the renewable energy but also aims to introduce some innovations such as the use of Super-Lift Luo-Converter and closed-loop control. It is therefore hoped that the solar panel power system herein designed will have good prospects for application.